Hubungan Paritas Terhadap Kejadian Anemia Pada Ibu Hamil di Kecamatan Gebang Kabupaten Jember - Anggun Lestari, Dwi (MEDICAL JURNAL OF AL-QODIRI, 2020)
In 2017 the maternal mortality rate in Indonesia reached 4,167 people, in East Java in 2017 there were 91.92 / 100,000 live births and in Jember there were 41% / 100,000 live birth in 2018. As for the causes of maternal death, among others the occurrence of bleeding during delivery, preeclampsia during pregnancy and postpartum infection. The incidence of anemia in expectant motheris a factor in the occurrence of bleeding during childbirth and the occurrence of infections after childbirth which in turn is the cause of the increase in maternal mortality. And what can cause a pregnant woman to experience anemia is because often a woman gives birth, either still gives birth or lives in large numbers, because the more often the mother gives birth, the more the mother loses iron. This study aims to analyze the relationshipa mother giving birth to a dead or living child in large numbers with the occurrence of anemia at pregnant mother in Gebang district, Jember Regency. The research design used is a correlative study through a cross sectional approach. The population used inside the study were expectant mother in Gebang District from August to September 2020 with a total of 261 people and the sample used in this study was 80 people. In this data analysis test used is a technique that analyzes data on 1 variable independently through frequency distribution and analyzes 2 variables through Chi-Square statistical test. From the results of the analysis test on 80 pregnant mother, the result is thatalmost part that is as much46.2%experienceanemia during pregnancy and most, namely 61% of expectant mother with high parity. And based on the results of the Chi-Square statistical test, it was found that the p-value was 0.012 (<0.05), which has meaning that there is a relationship between mothers who gave birth to many children toagainst anemia in expectant mother. Mothers experience parity will have the risk of anemia during pregnancy which eventually causes bleeding complications during delivery and the risk of bleeding during subsequent pregnancies, as a result of a decrease in hemoglobin levels during pregnancy. Thus, it is hoped that health officercould be more active inside provideespionage for expectant mother as an effort to avoid and get at anemia in expectant mother. Key words: incidence of anemia, parity, pregnant wom